Achimota Pararubulavirus 3: A New Bat-Derived Paramyxovirus of the Genus Pararubulavirus - Kate S. Baker; Mary Tachedjian; Jennifer Barr; Glenn A. Marsh; Shawn Todd; Gary Crameri; Sandra Crameri; Ina Smith; Clare E.G. Holmes; Richard Suu-Ire; Andres Fernandez-Loras; Andrew A. Cunningham; et al. (Viruses, 2020)
Bats are an important source of viral zoonoses, including paramyxoviruses. The paramyxoviral Pararubulavirus genus contains viruses mostly derived from bats that are common, diverse, distributed throughout the Old World, and known to be zoonotic. Here, we describe a new member of the genus Achimota pararubulavirus 3 (AchPV3) and its isolation from the urine of African straw-coloured fruit bats on primary bat kidneys cells. We sequenced and analysed the genome of AchPV3 relative to other Paramyxoviridae, revealing it to be similar to known pararubulaviruses. Phylogenetic analysis of AchPV3 revealed the failure of molecular detection in the urine sample from which AchPV3 was derived and an attachment protein most closely related with AchPV2—a pararubulavirus known to cause cross-species transmission. Together these findings add to the picture of pararubulaviruses, their sources, and variable zoonotic potential, which is key to our understanding of host restriction and spillover of bat-derived paramyxoviruses. AchPV3 represents a novel candidate zoonosis and an important tool for further study.